Levantamento da intensidade da alternariose e da podridão negra em cultivos orgânicos de brássicas e longevidade da esporulação de Alternaria brassicicola em restos foliares de brócolis - PERUCH, Luiz Augusto Martins (2004)
The brassica cultivation has been of high importance in Brazil. However, the profitable crop production can be limited by occurrence of diseases such as Alternaria black spot, caused by Alternaria brassicicola and/or Alternaria brassicae, and black rot, caused by Xanthomonas campestris pv. campestris. In that context, the present study had as objectives to evaluate the intensity of Alternaria black spot and of black rot diseases on brassica under organic cultivation in the states of Pernambuco and Santa Catarina, and the spore production longevity of A. brassicicola in leaf debris of broccolis. The intensity of the diseases was evaluated from November 2001 to February 2002, in 103 fields under organic farming systems, including broccoli, Chinese cabbage, cauliflower, kale and cabbage. High prevalence of the diseases was registered in both states, except on Chinese cabbage in Santa Catarina. Prevalence of Alternaria black spot was 100% on broccoli fields in Pernambuco, as well as on cauliflower in the two states, while the black rot reached that level on broccoli and cauliflower fields in Santa Catarina. In the average of the different brassica species, the diseases were more prevalent in Pernambuco than in Santa Catarina. However, when considered severity averages of each disease, no significant differences were verified between the two states, although the climatic conditions have been sharply different. The levels ofdisease severity were low, considering that 98% of the fields presented severity lower than 5%. The Alternaria black spot severity varied among the brassica species in Pernambuco, being higher on Chinese cabbage and lower on kale. In Santa Catarina no significant differences were verified among the brássicas species. In relation to the black rot, only in Santa Catarina there was difference in the disease severity among the brassicas, being registered the lowest level on Chinese cabbage. No significant correlations were verified between severity levels of Alternaria black spot and black rot, neither between disease severity and total number of plants or plant age. The spore production longevity of A. brassicicola was investigated in leaves debris of broccoli, considering different depths of debris incorporation, periods of the year, and systems of soil handling, in two experiments carried out in Urussanga city, State of Santa Catarina, Brazil. Infected leaves debris of broccoli were conditioned in bags of polyethylene and distributed in portions in the field, on the soil surface and at depths of 5 and 10 cm. Periodically, the debris in the bags were collected and conidia concentrations were quantified for longevity of spore production andextinction rate. In both experiments there was higher spore production longevity in leaves debris in the period I, characterized by lighter temperatures, higher air relative humidity and lower pluvial precipitation than in the period II. Depth of debris incorporation influenced directly on A. brassicicola spores production, being lower when incorporation was made at 10 cm depth. In relation to soil handling systems, when the inoculum source was deposited on the soil surface there was not difference in the rate of spore production extinction between the soils under conventional and organic handling. However, at depths of 5 and 10 cm, the rate was significantly higher in the soil under conventional handling. The management of Alternaria black spot on broccoli at the area under study can be accomplished by integrated control, including the incorporation of infected leaves debris in the soil, at least 10 cm depth, along with crop rotation, for no less than a 60-day interval in subsequent brassica plantings.